2015
DOI: 10.1002/stc.1754
|View full text |Cite
|
Sign up to set email alerts
|

Impact damage identification in composite skin-stiffener structures based on modal curvatures

Abstract: Summary The feasibility of a vibration‐based damage identification approach for impact damage in two advanced composite skin‐stiffener structures is investigated in this paper. Mode shape curvatures combined with the modal strain energy damage index (MSE‐DI) algorithm are utilized to identify the damage. Special attention is paid to the effective application of this vibration‐based methodology by investigating the relation between the damage location, the structural design, and the dynamic behavior. The perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Because of the highly sensitive characteristic to local defects, modal curvature and/or modal strain based quantities have been widely utilized to identify the presence, locations, and severity of damage in dynamic structures by the comparisons of before and after damage [23][24][25][26]. For the assessment of structural status, modal macrostrain vectors, macrostrain frequency response functions, and modal curvatures were successfully applied in structural health monitoring [27,28]. Furthermore, for dynamic stresses analysis, Pelayo et al [29] proposed a modal-based method in which the SMSs play a key role.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…Because of the highly sensitive characteristic to local defects, modal curvature and/or modal strain based quantities have been widely utilized to identify the presence, locations, and severity of damage in dynamic structures by the comparisons of before and after damage [23][24][25][26]. For the assessment of structural status, modal macrostrain vectors, macrostrain frequency response functions, and modal curvatures were successfully applied in structural health monitoring [27,28]. Furthermore, for dynamic stresses analysis, Pelayo et al [29] proposed a modal-based method in which the SMSs play a key role.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…Several advantages and limitations of these methods were also pointed out. Many studies confirm that mode shapes and corresponding mode shape curvatures are highly sensitive to damage and can be used for detection and quantification of the damage. Maia et al in performed extensive numerical simulations on a beam structure to compare damage identification sensitivity within different methods, based on the changes of mode shape, mode shape slope, mode shape curvature and mode shape curvature square, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that this algorithm is successful, although the data obtained from impact testing were classified with higher accuracy than that obtained with a shaker. Dworakowski et al in used a digital image correlation to build a deflection curve of a cantilevered beam. After the introduction of damage, these curves were fitted to two line segments, and an angle between segments was taken as a damage index.…”
Section: Introductionmentioning
confidence: 99%
“…Wave propagation properties mainly depend on their attenuation properties and waveform characteristics [9][10][11]. Vibration modes and related methods are more commonly used, including natural frequency and frequency response function spectrum (FRFs) based methods [12][13][14][15], mode shape based methods [16], mode shape curvature/strain mode shape based methods [17,18], model and related matrix based methods [19], and data driven methods [20]. Some signal processing techniques are proposed for the extraction of vibration characteristics [21].…”
Section: Introductionmentioning
confidence: 99%